2021
DOI: 10.1038/s41467-021-25551-1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level inhibition of coronavirus replication by chemical ER stress

Abstract: Coronaviruses (CoVs) are important human pathogens for which no specific treatment is available. Here, we provide evidence that pharmacological reprogramming of ER stress pathways can be exploited to suppress CoV replication. The ER stress inducer thapsigargin efficiently inhibits coronavirus (HCoV-229E, MERS-CoV, SARS-CoV-2) replication in different cell types including primary differentiated human bronchial epithelial cells, (partially) reverses the virus-induced translational shut-down, improves viability o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 113 publications
4
90
0
Order By: Relevance
“…The evolution of a viral mechanism to counteract the effects of ER-stress is consistent with the emergent notion that UPR provides a crucial contribution to the activation of innate antiviral signaling, as seen with flaviviruses (279). Strikingly, treatment of cells with thapsigargin, a guaianolide which induces ER-stress by inhibiting the ER Calcium ATPase, represses replication of SARS-CoV-2 and other CoVs, counteracts virus mediated BiP downregulation, activates IRE1α and outweighs coronavirus mediated inhibition of global protein synthesis, thus becoming an attractive antiviral drug candidate (278,280).…”
Section: The Interaction Of Orf3a With the Apoptosis And Autophagy Pathwayssupporting
confidence: 77%
See 1 more Smart Citation
“…The evolution of a viral mechanism to counteract the effects of ER-stress is consistent with the emergent notion that UPR provides a crucial contribution to the activation of innate antiviral signaling, as seen with flaviviruses (279). Strikingly, treatment of cells with thapsigargin, a guaianolide which induces ER-stress by inhibiting the ER Calcium ATPase, represses replication of SARS-CoV-2 and other CoVs, counteracts virus mediated BiP downregulation, activates IRE1α and outweighs coronavirus mediated inhibition of global protein synthesis, thus becoming an attractive antiviral drug candidate (278,280).…”
Section: The Interaction Of Orf3a With the Apoptosis And Autophagy Pathwayssupporting
confidence: 77%
“…If from one side it appears that the interaction between SARS-CoV-2 proteins and UPR effectors leads to the activation of this stress response, another recent article suggests that, even though CoVs infection initiate ER stress signaling and induces UPR components at the mRNA level, these are inhibited at the protein level (278). This could indicate that coronaviruses, including SARS-CoV-2, might have evolved strategies acting at posttranscriptional or translational level to escape antiviral response placed by BiP, IRE1α, and HERPUD.…”
Section: The Interaction Of Orf3a With the Apoptosis And Autophagy Pathwaysmentioning
confidence: 99%
“…We previously showed that the antiviral use of TG was highly effective against influenza viruses of different subtypes [ 12 ], respiratory syncytial virus, coronavirus OC43 and an original isolate of SARS-CoV-2 (2019-nCoV/Italy-INMI1, clade V) [ 11 ]. Other groups have reported effective TG inhibition of paramyxoviruses [ 18 ], and 229E, Middle-East respiratory syndrome and SARS-CoV-2 coronaviruses [ 19 ]. All available data (generated by us and others) as exemplified in influenza virus, RSV and coronaviruses, including SARS-CoV-2, indicate that TG does not prevent viral entry but rather triggers intracellular pathways to inhibit virus replication [ 11 , 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have reported effective TG inhibition of paramyxoviruses [ 18 ], and 229E, Middle-East respiratory syndrome and SARS-CoV-2 coronaviruses [ 19 ]. All available data (generated by us and others) as exemplified in influenza virus, RSV and coronaviruses, including SARS-CoV-2, indicate that TG does not prevent viral entry but rather triggers intracellular pathways to inhibit virus replication [ 11 , 12 , 19 ]. As a host-centric antiviral, TG hits several central host mechanisms connected to endoplasmic reticulum stress-unfolded protein response to inhibit several stages of virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…PEDV and TGEV infect and destroy villous epithelial cells of the jejunum and ileum, resulting in lethal watery diarrhea and piglet dehydration (Van Nieuwstadt et al, 1989;Cruz et al, 2011). The two human α-coronavirus (HCoV-229E and HCoV-NL63) cause mild symptoms mainly restricted to the upper respiratory tract (Shaban et al, 2021). Human coronaviruses (SARS-CoV, SARS-CoV-2 and MERS-CoV) are a member of β-coronavirus.…”
Section: Introductionmentioning
confidence: 99%